HASIL BELAJAR IPS SISWA SMP TERBUKA JAKARTA - ., Nurhayati (Jurnal Teknologi Pendidikan, 2013)
The objective of the research was to study the relationship between Reading Comprehension Ability, Self Learning, The Utilization of Learning Resources with IPS Learning Outcome. The study was carried out at Open Junior High School DKI Jakarta. The study utilized survey method. The sample size was 90 taken Multi Stage Sampling from the population. The data were collected using instrument in form of test and questioner. The data were analyzed using multiple regression and statistical correlation technique. The research concludes that there are positive correlation between: 1) Reading Coprehension Ability with IPS Learning Outcome, 2) Self Learning with IPS Learning Outcome, 3) The function of Learning Resources with IPS Learning Outcome. Futhermore, the research finds out that there is positive correlation between those three independent variables with IPS Learning Outcome. Therefore to improve IPS Learning Outcome can be carried out by improving Reading Comprehension Ability, Self Learning and The Utilization of Learning Resources.